Effect of Macrolide Prophylactic Therapy on AIDS-Defining Conditions and HIV-Associated Mortality. (1st April 2019) - Pasayan, Mark Kristoffer U.; S. Mationg, Mary Lorraine; Boettiger, David; Lam, Wilson; Zhang, Fujie; Ku, Stephane Wen-Wei; Merati, Tuti Parwati; Chaiwarith, Romanee; Cuong, Do Duy; Yunihastuti, Evy; Kiertiburanakul, Sasisopin; Van Kinh, Nguyen; et al.
Abstract : Background: Mycobacterium avium complex prophylaxis is recommended for patients with advanced HIV infection. With the decrease in incidence of disseminated Mycobacterium avium complex infection and the availability of antiretroviral therapy (ART), the benefits of macrolide prophylaxis were investigated. This study examined the impact of macrolide prophylaxis on AIDS-defining conditions and HIV-associated mortality in a cohort of HIV-infected patients on ART. Methods: Patients from TREAT Asia HIV Observational Database (September 2015 data transfer) aged 18 years and older with a CD4 count <50 cells/mm 3 at ART initiation were included. The effect of macrolide prophylaxis on HIV-associated mortality or AIDS-defining conditions (as a combined outcome) and HIV-associated mortality alone were evaluated using competing risk regression. Sensitivity analysis was conducted in patients with a CD4 <100 cells/mm 3 at ART initiation. Results: Of 1345 eligible patients, 10.6% received macrolide prophylaxis. The rate of the combined outcome was 7.35 [95% confidence interval (CI): 6.04 to 8.95] per 100 patient-years, whereas the rate of HIV-associated mortality was 3.14 (95% CI: 2.35 to 4.19) per 100 patient-years. Macrolide use was associated with a significantly decreased risk of HIV-associated mortality (hazard ratio 0.10, 95% CI: 0.01 to 0.80, P = 0.031) but not with the combined outcome (hazard ratio 0.86, 95% CI: 0.32 to 2.229, P = 0.764). Sensitivity analyses showed consistent results among patients with a CD4 <100 cells/mm 3 at ART initiation. Conclusions: Macrolide prophylaxis is associated with improved survival among Asian HIV-infected patients with low CD4 cell counts and on ART. This study suggests the increased usage and coverage of macrolide prophylaxis among people living with HIV in Asia. Abstract : Supplemental Digital Content is Available in the Text.